2016
DOI: 10.1128/cvi.00395-16
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Robust Immune Responses in Swine by Using a Cocktail of Adenovirus-Vectored African Swine Fever Virus Antigens

Abstract: eThe African swine fever virus (ASFV) causes a fatal hemorrhagic disease in domestic swine, and at present no treatment or vaccine is available. Natural and gene-deleted, live attenuated strains protect against closely related virulent strains; however, they are yet to be deployed and evaluated in the field to rule out chronic persistence and a potential for reversion to virulence. Previous studies suggest that antibodies play a role in protection, but induction of cytotoxic T lymphocytes (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
69
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(80 citation statements)
references
References 37 publications
(59 reference statements)
4
69
0
Order By: Relevance
“…The identified adhesion probability scores for EP402R (CD2v) (score 0.457) and EP153R (score 0.372) correlate with previous reports that have shown that these proteins are involved in ASFV hemadsorption (HA) in vitro (Borca et al, 1998(Borca et al, , 1994bGalindo et al, 2000;Neilan et al, 1999;Rodríguez et al, 1993;Ruiz-Gonzalvo et al, 1996). Adhesion probability scores were identified for B646L/p72 (score 0.25), CP204L/p30 (score 0.363), and E183L/p54 (score 0.566), all previously reported to be potential protective antigens (Argilaguet et al, 2012;Gómez-Puertas et al, 1998;Lokhandwala et al, 2016;Neilan et al, 2004). A 20% weight for each MHC class epitopes was chosen to select both classes of epitopes equally to maximize immunogenicity potential.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…The identified adhesion probability scores for EP402R (CD2v) (score 0.457) and EP153R (score 0.372) correlate with previous reports that have shown that these proteins are involved in ASFV hemadsorption (HA) in vitro (Borca et al, 1998(Borca et al, , 1994bGalindo et al, 2000;Neilan et al, 1999;Rodríguez et al, 1993;Ruiz-Gonzalvo et al, 1996). Adhesion probability scores were identified for B646L/p72 (score 0.25), CP204L/p30 (score 0.363), and E183L/p54 (score 0.566), all previously reported to be potential protective antigens (Argilaguet et al, 2012;Gómez-Puertas et al, 1998;Lokhandwala et al, 2016;Neilan et al, 2004). A 20% weight for each MHC class epitopes was chosen to select both classes of epitopes equally to maximize immunogenicity potential.…”
Section: Discussionsupporting
confidence: 84%
“…In contrast, pigs that were administered MVA-ASFV construct cocktails failed to generate detectable ASFV antibody responses. This outcome was somewhat unexpected since this expression system elicited antibodies when used with other antigens (Brewoo et al, 2010) and another viral-vector system (human adenovirus 5) elicited antibodies when used with some of the same (E183L, B646L) antigens (Lokhandwala et al, 2016). The lack of antibody response may be related to a defect in antigen presentation, e.g., the retention of the MVA expressed ASFV antigens inside infected cells may have limited their presentation to B-cells (Borrego et al, 2006;Ganges et al, 2005).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…A large number of studies have demonstrated that virus vectored vaccine can induce strong specific antibody-mediated humoral responses and IFN-γ secreting cellular responses in pigs, which can provide partial effective protection against ASFV challenge [ 96 , 97 , 98 ]. In 2019, as shown in Table 4 , Lokhandwala’s group evaluated the immune response and protective effect induced by two recombinant adenovirus combinations, Ad-ASFV-I (A151R, B119L, B602L, EP402R∆PRR, B438L, K205R, A104R, pp62, and p72) and Ad-ASFV-II (p30, p54, pp62, p72, and pp220), by intranasal challenge of ASFV-Georgia 2007/1 on the basis of previous studies.…”
Section: Current State Of Asf Vaccine Developmentmentioning
confidence: 99%